Balancing and Lucas-Balancing Numbers and their Application to Cryptography - Sujata Swain; Chidananda Pratihary; Prasanta Kumar Ray (Universitas Sriwijaya, 2016)
It is well known that, a recursive relation for the sequence Â is an equation that relates Â to certain of its preceding terms . Initial conditions for the sequence Â are explicitly given values for a finite number of the terms of the sequence. The recurrence relation is useful in certain counting problems like Fibonacci numbers, Lucas numbers, balancing numbers, Lucas-balancing numbers etc. In this study, we use the recurrence relations for both balancing and Lucas-balancing numbers and examine their application to cryptography.